The Tet2–Upf1 complex modulates mRNA stability under stress conditions - Xia, Meiling; Yan, Rui; Wang, Wenjuan; Kong, Anqi; Zhang, Meng; Miao, Zhigang; Ge, Wei; Wan, Bo; Xu, Xingshun (Frontiers in Genetics, 2023)
Environmental stress promotes epigenetic alterations that impact gene expression and subsequently participate in the pathological processes of the disorder. Among epigenetic regulations, ten-eleven translocation (Tet) enzymes oxidize 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) in DNA and RNA and function as critical players in the pathogenesis of diseases. Our previous results showed that chronic stress increases the expression of cytoplasmic Tet2 in the hippocampus of mice exposed to chronic mild stress (CMS). Whether the cytoplasmic Tet2 alters RNA 5hmC modification in the chronic stress-related processes remains largely unknown. In this study, we found that increased cytoplasmic Tet2 expression under CMS conditions leads to increased total RNA 5hmC modification. Tet2 interacted with the key nonsense-mediated mRNA decay (NMD) factor upstream frameshift 1 (Upf1), regulated the stability of stress-related genes such as Unc5b mRNA by regulating RNA 5hmC modification, and might thereby affect neurodevelopment. In summary, this study revealed that Tet2-mediated RNA 5hmC modification is involved in stress-related mRNA stability regulation, and may serve as a potential therapeutic target for chronic stress-related diseases such as depression.